Being a tough person in a tight world: Cultural tightness leads to a desire for muscularity - Chen, H.; Wang, X.; Zang, H.; Guinote, A. (Journal of Experimental Social Psychology, 2021)
Compared to loose cultures, tight cultures are characterized by stronger norm adherence and sanctioning of norm deviant behavior. In the current research, we proposed that culture tightness (vs. looseness) triggers a desire for physical formidability (being big and muscular), and interpersonal dominance. Fives studies converged to support our hypotheses. Through the analysis of archival data of over 1.6 million American residents, Study 1 showed that compared to those in loose states, individuals living in tight ones have a bigger body size (higher BMI), a correlate of muscle mass and strength. Studies 2–5 (N = 1626) further demonstrated a causal relationship. As such, placing people in a simulated tight society increased their drive for muscularity of the self (but not for body fat, Studies 2 and 3, nor for others’ muscularity, Study 3). This effect was further replicated in the following studies using a different manipulation method for cultural tightness (Studies 4 and 5). In addition, we found that a desire for dominance acted as a mediator in this process (Studies 4 and 5). We also differentiated dominance from a related concept – prestige (Study 5), and discussed contributions of these findings for the understanding of culture tightness-looseness.